FROM GLOBAL FRAMEWORKS TO LOCAL CLASSROOMS NEGOTIATING CEFR-BASED ENGLISH MATERIALS IN A PESANTREN-BASED UNIVERSITY - Faiz Rizki Muhammad; Haris Munandar; Dinar Dipta (English Education Study Program STKIP PGRI Pacitan, 2026)
The adoption of the Common European Framework of Reference for Languages (CEFR) has become increasingly prevalent in higher education institutions seeking to enhance educational quality and align language learning outcomes with international standards. However, the implementation of CEFR-based materials in culturally distinctive educational environments requires continuous negotiation between global frameworks and local realities. This study investigates how a pesantren-based university in Indonesia adopts, adapts, and implements CEFR-oriented English materials within its Language Class Program (LCP). Using a qualitative case study design, data were collected through semi-structured interviews with program administrators and tutors, classroom observations, and document analysis. The findings reveal three major themes: (1) CEFR as an institutional strategy for internationalization, (2) the localization of imported CEFR materials within the pesantren context, and (3) the mediating role of tutors in translating global standards into meaningful classroom practices. The study demonstrates that CEFR implementation is not a process of direct adoption but rather a dynamic negotiation in which global language policies are reinterpreted according to local educational values, institutional goals, and learners’ needs. The findings contribute to discussions on curriculum internationalization, language policy enactment, and material localization in Islamic higher education.